Power generation equipment

JP7637977B2Active Publication Date: 2025-03-03KAFU365 CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021087195
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-24
Publication Date
2025-03-03
Estimated Expiration
2041-05-24

AI Technical Summary

Benefits of technology

【0017】 本発明の発電装置は、特殊な資材を必要とせず、構造が簡単であり、比較的安価に製造できる。また、発電のために燃料を必要としないから、排気汚染、廃棄物汚染物などを放出しないので環境破壊を生じない。また更に、化学的および物理的消耗がなく、放射線をエネルギーとして発電効果が継続的になされるので経済的な電力が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637977000009
    Figure 0007637977000009
  • Figure 0007637977000001
    Figure 0007637977000001
  • Figure 0007637977000002
    Figure 0007637977000002
Patent Text Reader

Abstract

To provide power generation equipment which does not discharge carbon dioxide gas, radioactivity, radioactive contaminants or the like and is thus not susceptible to environmental destruction.SOLUTION: Power generation equipment includes porous material radicalizing water vapor adsorbed in pores by natural radiation, a hydratable inorganic solidification agent, and an electrically conductive additive.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a power generation device for obtaining electrical energy by utilizing cosmic rays (radiation arriving from outer space). [Background technology]

[0002] Electrical energy is essential to human life, but power generation equipment that relies on thermal or nuclear power not only generates carbon dioxide and radioactivity, but also emits by-products such as radioactive contaminants (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2020-043753 Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made in consideration of the above problems, and aims to provide a power generation device that does not emit carbon dioxide gas, radioactivity, radioactive contaminants, etc., and that does not pose a risk of environmental destruction. [Means for solving the problem]

[0005] In order to achieve the above object, the power generation device of the present invention is configured to include a porous substance that radicalizes water vapor adsorbed inside the pores using natural radiation, a hydratable inorganic solidifying agent, and an electrically conductive additive.

[0006] Microporous materials have the property of adsorbing liquids, gases, and water vapor, and the interior of the pores is filled with adsorbed water vapor from the atmosphere, which undergoes a radical reaction when irradiated with radiation from space, generating ions. Therefore, the present invention solves the above problem by polarizing this charge and extracting it as electricity.

[0007] Below is a list of the items required to complete a power generation device that can continue to generate electric charges and efficiently extract power.

[0008] (1) Microporous materials include various carbons, zeolites, and diatomaceous earths, which are involved in the radical reaction to some extent. However, zeolites and diatomaceous earths, which have unpaired electrons in their atomic frameworks, are electrically conductive and convert the electric charge generated by the reaction into heat. Therefore, electric charge cannot be stored in the pores for a long period of time, making it difficult to continuously polarize and extract the electric charge over a long period of time.

[0009] On the other hand, charcoal and bamboo charcoal are amorphous carbon allotropes with no unpaired electrons in their atomic skeletons, and because they are insulating materials, they do not convert the ions (charges) generated by radical reactions into heat. In other words, they can store charges in their pores for long periods of time, allowing them to polarize and extract the charges continuously over long periods of time.

[0010] For the above reasons, the microporous material used in the present invention is preferably charcoal or bamboo charcoal, but zeolite can also be used in a limited capacity as a short-term power generator.

[0011] (2) In order to increase the amount of ions (charges) obtained by the radical reaction occurring within the pores of the porous material, the particles of the porous material are bonded together and solidified to converge and increase the accumulated ions between the particles, and in this invention, a solidifying agent is used to form a solidified material.

[0012] Here, since organic solidifying agents are electrically insulating, in the present invention, an inorganic hydratable substance is used as the solidifying agent.

[0013] (3) In addition, in the present invention, in order to converge the electric charges generated in the microporous material in the solidified material and guide them to the electrode, electrical conductivity is imparted to the solidifying agent. A suitable method for imparting electrical conductivity is to use water of crystallization of cement bacillus. Another suitable method for imparting electrical conductivity is to add and mix an electrically conductive substance to the solidifying agent to form an electrically conductive solidified material.

[0014] (4) In order to polarize the electric charge and extract electric power, it is preferable to use two kinds of metal pieces having different ionization tendencies in contact with the solidified material.

[0015] (5) Furthermore, in order to promote the radical reaction occurring in the micropores in the solidified material, it is preferable to improve the circulation of the water vapor mass. Therefore, in the present invention, it is preferable to use a foaming agent or air-entraining fibers in combination during solidification to provide holes through which the water vapor mass in the atmosphere can pass and promote the radical reaction.

[0016] (6) In order to excite the radical reaction occurring in the pores of the microporous material and increase the electric power, it is preferable to bring a semiconductor ceramic or a radioactive material into contact with or in the vicinity of the solidified material. [Effects of the Invention]

[0017] The power generation device of the present invention does not require special materials, has a simple structure, and can be manufactured relatively inexpensively. Furthermore, since it does not require fuel to generate electricity, it does not emit exhaust pollution or waste pollutants, and therefore does not cause environmental damage. Furthermore, there is no chemical or physical consumption, and the power generation effect is continuous using radiation as energy, so it can generate electricity economically.

[0018] This power generation device can be miniaturized and can be connected in layers to obtain electrical output, making it suitable for use in a wide range of electrical equipment, from small to large. Furthermore, this device can generate electricity regardless of whether it is in the dark, in the air, underwater, or underground, making it a valuable device that will greatly contribute to society. [Brief explanation of the drawings]

[0019] [Figure 1] FIG. 10 is a cross-sectional view showing an embodiment in which spherical radioactive material is placed between metal plates and fixed with adhesive. DETAILED DESCRIPTION OF THE INVENTION

[0020] The following describes the embodiments of the invention, and all quantities in the description are by weight (parts) unless otherwise specified. The power generation device of the embodiment is composed of five elements: a porous material having many macropores (hereinafter simply referred to as the porous material), a hydratable inorganic solidifying agent (hereinafter simply referred to as the solidifying agent), additives (solidifying agents include conductive materials, radioactive materials, semiconducting ceramics, foaming agents, air-entraining materials (fibers), acids, salts, and other additives), polarization metals (electrodes), and a power generation excitation device (semiconducting ceramics and radioactive materials).

[0021] The porous material used in the present invention has the function of radicalizing the mass of water vapor adsorbed inside the pores by natural radiation. Here, radicalization means that a mass of one molecule of water vapor (H2O) is radicalized by radiation (gamma rays) to hydrogen (H) + and hydroxyl group (OH) - These radicals instantly polymerize with each other, forming two hydrogen atoms (2H) +2 and hydroxyperoxide (H2O2) -2 It is known that ions associated with

[0022] Here, the porous substance used in the present invention is a carbon (hereinafter simply referred to as charcoal) that belongs to the amorphous carbon structure that does not have unpaired electrons in the atomic skeleton, and is a substance that has pores and has adsorptive properties. Since there are no unpaired electrons, it is insulating, and since the ions cannot be converted into heat, it can be maintained in a charged state.

[0023] Carbon that can store electricity includes charcoal, bamboo charcoal, coconut shell charcoal, etc., and can be one or a mixture of two or more types from these groups. Carbon with many pores and a large non-surface area is preferable, but there are no restrictions on the quality or shape.

[0024] Another porous material that can be involved in radical reactions is zeolite, which has a framework based on silicon oxide (SiO2). Zeolite here refers to crystalline aluminosilicate (general formula: M n+ x / n Al x Si Y O2x+2Yx ·zH2O).

[0025] However, because zeolite contains aluminum (Al) in its framework, it exhibits semiconducting properties and is not a perfect insulator, so it cannot maintain a charged state for a long period of time. In other words, the ions (charges) generated over time are lost, making it difficult to continuously extract a constant amount of electricity.

[0026] In order to extract the ions generated and stored in the porous material charcoal as a large charge, the ions generated in each charcoal particle must be converged and extracted.To achieve this, we propose combining and solidifying the individual charcoal particles using a solidifying agent.

[0027] However, solidifiers made of insulating materials cannot be used to concentrate ions due to their electrical conductivity. In other words, organic solidifiers cannot be used, so inorganic hydratable substances are used as solidifiers. Specifically, various cements, gypsum, lime, and calcium carbonate (which can be hydrated in an autoclave) are used as solidifiers, and in practice, one or a mixture of two or more types from these groups is used.

[0028] The particle size of the charcoal used in the present invention is preferably in the range of 0.01 to 10 mm in diameter, more preferably in the range of 0.1 to 5.0 mm. Particles with a size exceeding this range make it difficult to form a uniform composition when mixed with a solidifying agent.

[0029] The mixing ratio of charcoal to 100 parts by weight of the solidifying agent is not limited, but is preferably in the range of 5 to 150 parts by weight, and more preferably in the range of 50 to 100 parts by weight. If the ratio is outside this range, the power generation efficiency and strength may decrease.

[0030] The particle size of the zeolite used in this example is preferably in the range of 0.01 to 10 mm in diameter, more preferably in the range of 0.1 to 5.0 mm. Particles with a size exceeding this range make it difficult to form a uniform composition when mixed with a solidifying agent.

[0031] The mixing ratio of zeolite to 100 parts by weight of solidifying agent is not limited, but is preferably in the range of 10 to 250 parts by weight, and more preferably in the range of 50 to 200 parts by weight. If the ratio deviates from this range, power generation efficiency and strength may decrease. Note that the charcoal and zeolite can be combined in any weight ratio.

[0032] The solidifying agent is a hydratable substance such as Portland cement, alumina cement, gypsum, lime, or calcium carbonate (which can be hydrated in an autoclave), and is used in the form of a mixture of one or more of these. Furthermore, various chemicals can be mixed with the solidifying agent to form crystals such as Bacillus or Ettringite, and the resulting crystallized water can be used to improve electrical conductivity. To collect and extract the ions generated in each particle in the solidified material, conductive substances (such as various metals and carbon-containing substances), acids, salts, etc., are added.

[0033] In order to polarize and extract the charged ions in the solidified material, two metals with different ionization tendencies selected from the group consisting of Li (lithium), K (potassium), Ca (calcium), Na (sodium), Mg (magnesium), Al (aluminum), Zn (iron), Fe (iron), Ni (nickel), Sn (tin), Pb (lead), Cu (copper), Ag (silver), Pt (platinum), and Au (gold) are used as electrodes in contact with the solidified material. Note that the placement of the electrodes is optional and not limited.

[0034] In order to promote the radical reaction and increase the amount of generated charge, a semiconductor ceramic or a radioactive substance can be used as a power generation excitation device by contacting or placing it close to the solidified material, but the location of the attachment is not limited.

[0035] Semiconductor ceramics are ceramics that contain layers of different metal oxides (e.g., transition metal layers containing MnO2, NiO, CoO, CuO, etc., alumina layers, and silicate layers). In addition, to omit the installation of the power generation excitation device, materials that contain magnetic force or radiation may be granulated and mixed or used in combination with the solidifying agent.

[0036] The radioactive material is a radioactive mineral containing thorium, strontium, uranium, etc., at a level that is harmless to the human body, and specifically, a ceramic (radioactive ceramic ball) containing monasite can be mentioned. The power generation excitation device is constructed by combining a semiconductor ceramic and a radioactive material.

[0037] The procedure for producing the power generating device according to the embodiment will be described below, but the procedure is not limited to any particular order.

[0038] First, prepare a mold of the desired shape to form the solidified material in. Next, place the required amounts of porous material, solidifying agent, additives, and water in a container and mix and stir them in a mixer.

[0039] Next, the kneaded material is filled into the formwork and left for at least 24 hours to solidify. The solidified material is then demolded, and the solidified material is covered and protected with an electrically insulating protective material, leaving only the areas necessary for attaching the electrodes and excitation promotion device, as well as the area for supplying the steam mass. Finally, the electrodes and excitation device are attached to the solidified material. Figure 1 shows a cross-section of this device, with an example power generation excitation device (radioactive ceramic balls) attached.

[0040] The completed power generation device generates electricity continuously due to the radical reaction occurring within the pores of the porous material, and has the property of quickly recovering the power consumed by the load. The power generation effect of this device was stably obtained in the air, on the ground, underground, and underwater. In addition, this power generation device is lightweight and can be made compact, and devices can be connected in series or parallel.

[0041] Example 1 A 100 x 100 x 10 mm mold 1A was prepared, with a plastic frame and an aluminum base. Twenty-five 5 mm diameter spherical radioactive material particles were attached to the center of the base in a square arrangement spaced 2 cm apart. A composition consisting of bamboo charcoal with an average particle size of 3 mm, cement, gypsum, additives, and water was then poured into the mold. After 48 hours, a 10 x 10 x 0.5 mm copper plate was placed on top of the solidified material to measure the output voltage of the resulting solidified material 1A. A current was passed through a 1 kΩ load resistor, and the voltage across the load resistor and the current through the load resistor were measured using a Daiwa D-771 measuring instrument. The measurement results are shown in Table 1.

[0042] <Example 2> This example was the same as Example 1, except that no power generation excitation device (spherical radioactive material) was used. Specifically, a mold 2A measuring 100 x 100 x 10 mm was prepared, with a plastic frame and an aluminum bottom plate. The same composition as in Example 1 was then poured into the mold, and the output voltage of the resulting solidified material 2A was measured in the same manner as in Example 1 to test the effectiveness of the power generation excitation device. The composition of the solidified material 2A and the measured voltage and current are shown in Table 1.

[0043] Example 3 A composition consisting of zeolite with an average particle size of 3 mm, cement, gypsum, additives, and water was poured into the same mold 1A as in Example 1, which used 25 spherical radioactive materials, and the output voltage of the resulting solidified material 1B was measured in the same manner as in Example 1. The composition of solidified material 1B and the measured values ​​are shown in Table 1.

[0044] Example 4 The same composition as in Example 3 was poured into the same mold 2A as in Example 2, which did not use spherical radioactive material, and the output voltage of the resulting solidified material 2B was measured in the same manner as in Example 1 to test the effectiveness of the power generation excitation device. The composition and measured values ​​of solidified material 2B are shown in Table 1.

[0045] <Example 5> A composition consisting of charcoal, cement, gypsum, additives, and water with an average particle size of 3 mm was poured into the same mold 1A as in Example 1 using 25 spherical radioactive materials, and the output voltage of the resulting solidified material 1C was measured in the same manner as in Example 1. The composition of solidified material 1C and the measured values ​​are shown in Table 1.

[0046] Example 6 The same composition as in Example 5 was poured into the same mold 2A as in Example 2, which did not use spherical radioactive material, and the output voltage of the resulting solidified material 2C was measured in the same manner as in Example 1 to test the effectiveness of the power generation excitation device. The composition and measured values ​​of solidified material 2C are shown in Table 1.

[0047] Example 7 A composition consisting of a mixture of charcoal and zeolite with an average particle size of 3 mm, cement, gypsum, additives, and water was poured into the same mold 1A as in Example 1, which used 25 spherical radioactive materials, and the output voltage of the resulting solidified material 1D was measured in the same manner as in Example 1. The composition of the solidified material 1D and the measured values ​​are shown in Table 1.

[0048] Example 8 The same composition as in Example 7 was poured into the same mold 2D as in Example 2, which did not use spherical radioactive material, and the output voltage of the resulting solidified material 2D was measured to test the effectiveness of the power generation excitation device in the same manner as in Example 1. The composition and measured values ​​of the solidified material 2D are shown in Table 1.

[0049] [Table 1]

[0050] From the above examples, it was found that all solidified materials with a composition consisting of cement, gypsum, sodium bicarbonate, and wood vinegar in a porous substance can obtain a voltage of 1.0 V or more. Furthermore, from the above examples, it was found that the output voltage and current increase when a power generation excitation device is installed.

[0051] The power generation excitation device made of radioactive material used in the examples is a spherical particle with a diameter of 5 mm, and its component is a ceramic containing monasite ore (Mino Pigment Co., Ltd., product name: Iomix).

[0052] Example 9 A 100 x 100 x 10 mm mold 1A was prepared, with a plastic frame and an aluminum bottom plate. 25 spherical semiconductor ceramic particles, each 3 mm in diameter, were attached to the center of the bottom plate in a square arrangement spaced 2 cm apart to serve as a power generation excitation device. A composition consisting of bamboo charcoal with an average particle size of 3 mm, cement, gypsum, additives, and water was then poured into mold 3A. After 48 hours, a 10 x 10 x 0.5 mm copper plate was placed in contact with the top surface of the resulting solidified product as an electrode, and the output voltage was measured using the same tester as above.

[0053] The composition of the resulting solidified material 3A and the measured voltage are shown in Table 2. The semiconductor ceramics used were ceramics containing a metal oxide layer (transition metals including MnO2, NiO, CoO, CuO, etc., as well as alumina and silicates).

[0054] [Table 2]

[0055] The results of Examples 1 to 9 demonstrate that the power generation excitation device for semiconductor ceramics and radioactive materials operates effectively. The voltage generated by the solidified material produced in the above examples was measured over time. The measured values ​​are shown in Table 3.

[0056] [Table 3]

[0057] <Comparative Example> A composition consisting of porous material, cement, and water was poured into the same formwork as in Example 1, and the voltage generated by the resulting solidified material was measured in the same manner as in Example 1, but no voltage was detectable for any of the solidified materials. The composition of the solidified materials and the measured voltage values ​​are shown in Table 4.

[0058] [Table 4]

[0059] In Table 4, the compositions of Comparative Examples 1, 3, 5, and 7 are almost the same as those of Examples 1, 3, 5, and 7 in Table 1, except that aluminum phosphate, wood vinegar, and sodium bicarbonate are omitted.

[0060] Example 10 A 100 x 100 x 10 mm mold was filled with the same composition as solidified material 1A to create solidified material 4A. After 72 hours, a copper plate with low ionization tendency was placed in contact with the top surface of this solid, and a tester's anode probe was attached. Aluminum and iron, which have higher ionization tendency than copper, were placed in contact with the bottom surface, and the cathode probe was alternately placed in contact with each metal to measure the generated voltage. The results are shown in Table 5. However, no power generation excitation device was used in this experiment.

[0061] In this experiment, when the probe was inverted and brought into contact with the object, a negative voltage was displayed, indicating that a DC voltage was being generated.

[0062] [Table 5]

[0063] Example 11 To investigate the electrical conductivity of cement bacillus, we added sulfate compounds (calcium sulfate / gypsum) to cement and hydrated them in a carbon dioxide atmosphere to produce bacillus. We then compared the electrical conductivity (conductivity) with that of simple cement hydrate. Two PVC pipes, each 30 mm in diameter and 50 mm long, were prepared. One was filled with a cement-water composition, and the other with a composition consisting of cement, calcium sulfate, sodium bicarbonate, anhydrous cobalt chloride, and water. These cylindrical solids (A) and (B) were then prepared. The solids were then left in a room at 25°C for 10 days, allowed to dry, and their resistance values ​​were measured using a tester. The compositions and measured resistance values ​​(mΩ) of solids (A) and (B) are shown in Table 6. These results suggest that the amount of crystallized water increases with the formation of cement bacillus.

[0064] [Table 6]

[0065] Example 12 In order to ensure a vent hole that supplies the solidified material with a mass of water vapor to continue the radical reaction, hemp fiber (diameter: 0.08 mm, length: 1.5 mm) was added and mixed into the solidifying agent, and the change in output voltage over time was measured. The composition of the solidified material is shown in Table 7, and the measurement results are shown in Table 8.

[0066] [Table 7]

[0067] [Table 8]

[0068] The results of Example 12 showed that providing ventilation holes for the steam mass in the solidified material tends to result in efficient and stable power generation over the long term, and that using fibrous materials in combination is effective. Therefore, providing chemical or physical ventilation holes in the solidified material increases the power generation efficiency.

[0069] Although the embodiments of the present invention have been described in detail above, the inventor's view on the present invention is as follows.

[0070] <Radiation> Natural radiation is contained in cosmic rays and terrestrial radioactive materials and is known as alpha (α) rays, beta (β) rays, and gamma (γ) rays. Alpha and beta rays have low penetration properties, so alpha rays can be blocked with paper, and beta rays with a thin metal plate. However, gamma rays are so penetrating that they can only be blocked with a lead plate or a thick iron plate.

[0071] Gamma rays have the property of dissociating water vapor molecules (HO) in the air into hydrogen atoms (H) and hydroxyl groups (OH) (radical reactivity). An example of this is the Fukushima nuclear accident, which occurred in the past. The reactor was destroyed by a tsunami, and the large amount of hydrogen produced by the radical reaction of the powerful radiation exposed to the atmosphere exploded.

[0072] <Cosmic rays and microporous materials> Materials on Earth are constantly exposed to cosmic rays (magnetic field lines, infrared rays, ultraviolet rays, etc. are called radiation), and most materials are involved in converting this radiation into thermal energy. Charcoal and porous materials composed of micropores, such as zeolites (hereafter referred to as microporous materials), are no exception. However, carbon, which does not contain impurities in its crystalline atoms, does not have unpaired electrons in its atomic structure, so it does not have the properties of a semiconductor and is insulating. Zeolites differ from the above-mentioned carbon in their atomic structure, containing ring structures made of SiO or AlO bonds within their framework, and the interior of their pores is charged with sodium ions, giving them ion exchange capabilities. In other words, the above-mentioned carbon and zeolites differ in their electrical conductivity; the former is insulating and the latter is semiconductor.

[0073] <Radical reaction> In the radiation chemical reaction process, radiation (including natural radiation) dissociates water vapor masses (H2O) in the atmosphere, producing hydrogen (H) and hydroxyl groups (OH), so this reaction is called a radical reaction and the products are called radicals. Furthermore, it is known that the hydrogen in radicals carries an electron (-e) and has a strong ability to break organic bonds, while the hydroxyl group (OH) in radicals carries a strong electron (+e) and has strong oxidizing power.

[0074] <Microporous materials and power generation devices> Combining the above logic, it turns out that since microporous materials have excellent adsorption properties for liquids, gases, and water vapor, if radiation is applied to them while they adsorb water vapor from the atmosphere, ions (electrons) are generated within the pores. In other words, carbon, which does not contain impurities in its crystalline atoms, is an insulator and can store electrons within its layers, while zeolite is a semiconductor and has poor electron storage capabilities within its layers. Therefore, from here on, we will limit our discussion to electrons stored in the carbon mentioned above. If we could create a device that polarizes and extracts electrons stored within the carbon layers, it would be possible to generate electricity continuously using the infinite energy supply of radiation from space and water vapor in the atmosphere, and this could be called a power generation device.

[0075] <Requirements for power generation equipment> Considerations for completing the generator set include the following, along with material selection:

[0076] (1) Selection of microporous materials suitable for radical reactions. As mentioned above, carbon that does not have unpaired electrons in its atomic structure is desirable. More specifically, carbon allotropes include (A) diamond, (B) graphite, (C) lonsdaleite (hexagonal diamond), (D, E, F) fullerenes, and (G) amorphous carbon (charcoal, bamboo charcoal, coke, coal, peat, soot). From the standpoint of electrical conductivity and adsorption, it is desirable to use charcoal and bamboo charcoal, which belong to group G, either alone or in combination.

[0077] (2) A method of converging ions (electrons) produced by radical reactions. To converge the electrons generated in the charcoal and create a large electron collection, the charcoal particles must be bonded and solidified to converge the individual electrons. This requires the use of a conductive solidifying agent to bond and solidify the charcoal particles. Organic materials, being insulating, cannot be used as solidifying agents. Inorganic solidifying agents, such as hydratable solidifying agents like cement, gypsum, and lime, lose their electrical conductivity when they dry and lose moisture, thereby failing to achieve their intended purpose. Therefore, mixing or using conductive materials (e.g., metal powder, graphite powder, or other conductive powders) with hydratable solidifying agents is an option. However, contacting charcoal particles with conductive materials reduces their electron storage capacity, as with zeolites, and thus reduces their electron concentrating ability, making this method inapplicable.

[0078] Therefore, the researchers came up with the idea of ​​generating a large amount of crystalline water in the hardened cement, a substance that has high electrical conductivity and does not easily generate heat when electricity is passed through it, to concentrate electrons. To generate a large amount of crystalline water in the hardened cement, cement bacillus is generated. This results in cement bacillus that contains two to three times the amount of crystalline water contained in the solidified cement. The amount of crystalline water contained in the bacillus varies depending on the conditions of the bacillus generation process, but the electrical conductivity is at least improved compared to solidified cement alone.

[0079] Therefore, in order to ensure the production of cement bacillus, calcium sulfate is added to the cement, and as this maintains a carbon dioxide atmosphere during hardening, sodium bicarbonate (baking soda) is added, and an acidic substance (wood vinegar) is also added to prevent the cement from solidifying too quickly. The cement bacillus obtained in this way effectively solidifies and hardens the charcoal particles, allowing them to conduct convergent electrons efficiently.

[0080] (3) A method of polarizing electrons generated by radicals. Next, to polarize the focused electrons from the cement solidified material (cement bacillus bodies), metal pieces with different ionization tendencies are used as electrodes. A metal plate with a high ionization tendency (e.g., aluminum) is connected to one end of the solidified material, and a metal plate with a low ionization tendency (e.g., copper) is connected to the other end. This results in negative electrons being obtained at the metal electrode with the high ionization tendency, and positive electrons being obtained at the other metal electrode.

[0081] (4) A method for exciting radical reactions. When either a semiconducting ceramic or a radioactive material is placed close to or in contact with an electrode (metal plate) placed on the solidified material, or when the ceramic and radioactive material are mixed with the solidified material, the amount of electricity generated increases, so the conductive ceramic and radioactive material have the effect of stimulating the power generation effect. Here, the semiconducting ceramic is a ceramic containing layers of different metal oxides (e.g., transition metals including MnO2, NiO, CoO, CuO, etc., and alumina and silicates), and the radioactive material is a radioactive mineral containing thorium, strontium, uranium, etc., such as monasite.

[0082] (5) Conclusion To summarize the above, if cosmic rays are reacted with water vapor and converted into electricity, it can be used as energy; if charcoal, cement, gypsum, baking soda, wood vinegar, and two types of metal plates with different ionization tendencies are prepared, a power generation device can be obtained, and if semiconductor ceramics and radioactive materials are added, the amount of electricity generated can be increased. Since the key to generating a stable current is dependent on the radical reaction that occurs within the pores, if a large amount of water vapor (mass) is continuously supplied to the pores, power generation will continue and the power will increase.

Claims

1. The porous material is configured to convert water vapor adsorbed inside the pores into radicals by natural radiation, a hydratable inorganic solidifying agent, and an additive having electrical conductivity; A power generation device in which two types of metal pieces with different ionization tendencies are brought into contact with the inorganic solidifying agent, and the electric charge generated by the radicals is polarized and extracted.

2. 2. The power generating device according to claim 1, wherein the porous substance is a carbon type belonging to amorphous carbon having a structure that does not have unpaired electrons in the atomic skeleton, or a zeolite having a skeleton made of silicon dioxide (SiO2).

3. 3. The power generating device according to claim 1, wherein the inorganic solidifying agent bonds and solidifies the particles of the porous material to each other.

4. 4. The power generating device according to claim 1, wherein the inorganic solidifying agent is made to form cement bacillus (ettringite) crystals, and the resulting crystal water is used to improve the electrical conductivity.

5. A power generation device described in any one of claims 1 to 4, wherein one or more of conductive materials, radioactive materials, semiconductor ceramics, foaming agents, air-entraining materials (fibers), acids, and salts are mixed with the inorganic solidifying agent as the additive.

6. A power generating device described in any one of claims 1 to 5, wherein a semiconductor ceramic or a radioactive substance is installed as a power generating excitation device to promote the radicalization.

Citation Information

Patent Citations

  • Gamma ray electricity generating method

    JP2018100866A

  • Power generator

    JP2020043753A

  • Radiation-driven device including diamond material and power supply for radiation-driven device

    JP2020522681A

  • Nuclear radiation particle power converter

    US20150279491A1